2010
DOI: 10.1002/ardp.200900082
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and In‐Vitro Antitumor Activity of Some Pyrazolo[3,4‐b]pyridines and Pyrazolo[1,5‐a]pyrimidines Linked to a Thiazolo[3,2‐a]benzimidazole Moiety

Abstract: The key precursor E-3-(N,N-dimethylamino)-1-(3-methylthiazolo[3,2-a]benzimidazol-2-yl)prop-2-en-1-one 4 was synthesized in good yield using Gold's reagent. The reaction of enaminone 4 with 5-amino-3-aryl-1-phenylpyrazoles 5a, b in refluxing acetic acid in the presence of sulphuric acid, yielded pyrazolo[3,4-b]pyridines 7a, b. Similarly, pyrazolo[1,5-a]pyrimidines 10a, b and 14a-f were prepared by reaction of enaminone 4 with 5-amino-1H-pyrazoles 8a, b and 12a-f, respectively. The structure of pyrazolo[1,5-a]py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Several methods for the preparation of enaminones have been reported [24]. Enaminones 4a–j were efficiently prepared by the reaction of ketone 1a–j with dimethylformamide-dimethylacetal (DMF - DMA) ( 2 ) or with [3-(dimethylamino)-2-azaprop-2-en-1-ylidene] dimethylammonium chloride (Gold's reagent) (Scheme 1) ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for the preparation of enaminones have been reported [24]. Enaminones 4a–j were efficiently prepared by the reaction of ketone 1a–j with dimethylformamide-dimethylacetal (DMF - DMA) ( 2 ) or with [3-(dimethylamino)-2-azaprop-2-en-1-ylidene] dimethylammonium chloride (Gold's reagent) (Scheme 1) ( 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is necessity to improve the known analyses methods for this class of compounds or develop new methods. In continuation for our previous work [1924] in the chemistry of the title compounds, certain enaminones 4a–j were synthesized and used as model compounds for this current study.…”
Section: Introductionmentioning
confidence: 99%
“…1-(3-Methylthiazolo[3,2- a ]benzimidazol-2-yl)ethanone ( 10b ) was treated with dimethylformamide-dimethylacetal (DMF-DMA), in dry xylene, at reflux temperature, it afforded E -3-( N , N -dimethylamino)-1-(3-methylthiazolo[3,2- a ]benzimidazol-2-yl)prop-2-en-1-one ( 93 ) [ 70 ] ( Scheme 32 ). Recently, Abdel-Aziz et al reported an alternative synthesis of compound 93 using [3-(dimethyl-amino)-2-azaprop-2-en-1-ylidene]dimethylammonium chloride (Gold’s reagent) [ 71 ] where Gold's reagent reacted with ketone 10b in sodium methoxide to produce the enaminone 93 ( Scheme 32 ). The reaction of compound 93 with aminopyrazoles 94 in refluxing pyridine [ 70 ] or in acetic acid presence of H 2 SO 4 [ 71 ] afforded pyrazolo[1,5- a ]pyrimidines 95 .…”
Section: Chemical Transformationsmentioning
confidence: 99%
“…Recently, Abdel-Aziz et al reported an alternative synthesis of compound 93 using [3-(dimethyl-amino)-2-azaprop-2-en-1-ylidene]dimethylammonium chloride (Gold’s reagent) [ 71 ] where Gold's reagent reacted with ketone 10b in sodium methoxide to produce the enaminone 93 ( Scheme 32 ). The reaction of compound 93 with aminopyrazoles 94 in refluxing pyridine [ 70 ] or in acetic acid presence of H 2 SO 4 [ 71 ] afforded pyrazolo[1,5- a ]pyrimidines 95 .…”
Section: Chemical Transformationsmentioning
confidence: 99%
“…Because of the importance of pyrazolo[1,5‐ a ]pyrimidine scaffold, various methods for its synthesis have been developed. Most of them involve the condensation reaction between aminopyrazoles and 1,3‐ bis ‐electrophilic reagents, such as 1,2‐allenic ketones , enaminones , enaminonitriles , β‐ketonitriles , 1,3‐dicarbonyl compounds , and α,β‐unsaturated carbonyl compounds .…”
Section: Introductionmentioning
confidence: 99%